Strategi Komunikasi Islam Dalam Meningkatkan Pemahaman Ajaran Islam Masyarakat - Hamid Bashori, Abdul; Waeno, Mahamadaree; Maharani, Ivana Septian (STAI Publisistik Thawalib Jakarta, 2022)
Communication is key to understanding and addressing challenges in delivering da’wah messages. A da’i needs to master effective communication strategies to ensure that Islamic values are well-received by the community. This study aims to analyze the communication strategies used in Islamic da’wah to enhance understanding of Islamic teachings within society and to explore the influence of both verbal and non-verbal elements in effective da’wah communication. The research method employed is qualitative with a literature study approach. The results indicate that communication is an interactive process that influences others, both verbally and non-verbally, including through facial expressions, art, and technology. Islam, as a religion of da’wah, teaches communication that conveys the message of Allah Swt in a persuasive, educational, and informative manner. In Islamic communication, ethical principles are crucial, with sanctions and rewards as the foundation. Islamic communication strategies encompass various approaches, such as the carrot strategy (rewarding) and the sword strategy (punishing), to achieve practical da’wah goals. The objective is for the community to understand and apply Islamic teachings in their daily lives. In conclusion, Islamic communication strategies involve planning and management to achieve da’wah goals, the transmission of religious messages based on the Qur'an and Hadith, and the employment of various effective operational tactics.